Regular clinic attendance in two large San Francisco HIV primary care settings. Issue 5 (3rd May 2016) - Cohen, Jenny K.; Santos, Glenn-Milo; Moss, Nicholas J.; Coffin, Phillip O.; Block, Nikolas; Klausner, Jeffrey D.
ABSTRACT: Although poor clinic attendance is associated with increased morbidity and mortality among HIV-infected individuals, less is known about predictors of retention and the acceptability of targeted interventions to increase regular clinic attendance. To better understand which patients are at risk for irregular clinic attendance and to explore interventions to aid in retention to care, we surveyed patients attending two outpatient HIV clinics affiliated with the University of California, San Francisco. A total of 606 participants were surveyed, and the analysis was restricted to the 523 male respondents. Of this group, 45% ( N = 299) reported missing at least one visit a year. Missing a clinic visit was associated with being African American (aOR = 1.99; 95%CI 1.12–3.52), being a man who has sex with both men and women (aOR=2.72; 95%CI 1.16–6.37), and reporting at least weekly methamphetamine use (aOR=5.79; 95%CI 2.47–13.57). Participants who reported a monthly income greater than 2000 were less likely to miss an appointment (aOR = 0.56; 95%CI 0.34–0.93). Regarding possible retention interventions, most patients preferred phone calls over other forms of support. These findings support the need for ongoing engagement support with particular attention to at-risk sub-groups.